2009
DOI: 10.1371/journal.pone.0004659
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical Scientists' Perceptions of Ethical and Social Implications: Is There a Role for Research Ethics Consultation?

Abstract: BackgroundResearch ethics consultation programs are being established with a goal of addressing the ethical, societal, and policy considerations associated with biomedical research. A number of these programs are modelled after clinical ethics consultation services that began to be institutionalized in the 1980s. Our objective was to determine biomedical science researchers' perceived need for and utility of research ethics consultation, through examination of their perceptions of whether they and their instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 16 publications
3
25
0
Order By: Relevance
“…These perceptions were captured in a series of interviews and focus groups that explored life scientists’ views of the ethical and societal implications of their own work and of biomedical research in general. While other findings from these data have been previously reported, 28 this paper examines how life scientists think about accountability in research.…”
Section: Scientists’ Views Of Ethicsmentioning
confidence: 87%
“…These perceptions were captured in a series of interviews and focus groups that explored life scientists’ views of the ethical and societal implications of their own work and of biomedical research in general. While other findings from these data have been previously reported, 28 this paper examines how life scientists think about accountability in research.…”
Section: Scientists’ Views Of Ethicsmentioning
confidence: 87%
“…A score was attributed to nurses' answers to questions concerning the frequency of ethical issues. The scores were never (0), rarely (1), sometimes (2) and often (3). The summed scale score range was 0-30, where 0 indicated the least and 30 indicated the most experience with ethical problems.…”
Section: Experiences With Ethical Issuesmentioning
confidence: 99%
“…1,2 For this reason, in many European health facilities, ethics consultation services are being developed, and the debate about their role is growing stronger. 1,[3][4][5][6] Although numerous studies have demonstrated that most healthcare providers face recurrent ethical problems, institutions are not always able to effectively support nursing staff. 2 In particular, the limited availability of ethics consultation services, which has been reported by authors from different countries, fails to meet the frequent and strong requests by health workers to support their ethical difficulties in situations involving the terminally ill, patient autonomy and end-of-life decisions.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of the interaction is to provide information; identify, analyze, and/or deliberate about ethical issues; and recommend a course of action.” 79, p. 3 McCormick et al reported that psychiatric researchers were more likely than other researchers to find such services useful. 78 …”
Section: Introductionmentioning
confidence: 99%